Malignant transformation of well‐differentiated papillary mesothelioma 13 years after the diagnosis: a case report. (26th November 2013) - Costanzo, Luisa; Scarlata, Simone; Perrone, Giuseppe; Rossi, Luigi; Papa, Anselmo; Di Matteo, Francesco Maria; Tonini, Giuseppe; Onetti Muda, Andrea; Antonelli‐Incalzi, Raffaele; Tomao, Silverio
Abstract Well‐differentiated papillary mesothelioma (WDPM) is a rare mesothelial tumour affecting mostly the peritoneum of women in their reproductive age, but it may occur also at other sites, including the pleura. It is considered a specific pathological entity different from diffuse malignant mesothelioma as it displays a characteristic histological pattern and is associated with a slowly progressive clinical course. We report the case of a 79‐year‐old man with a history of right pleural WDPM at age 64, which was successfully treated with chemotherapy, radiotherapy and talc pleurodesis. Thirteen years after the first diagnosis, he presented with mediastinal lymph nodes metastasis and with an extremely rare pattern of tracheal and bronchial infiltration that was detected at bronchoscopy. Biopsy samples revealed loss of histological differentiation of the neoplastic cells. This case report highlights that WDPM is a tumour of uncertain malignant potential that may undergo transformation over many years. Finally, the role of immunohistochemistry in the diagnosis of WDPM and the possible mechanisms leading to this unique way of metastatisation are discussed.